Two Phases of Mitogenic Signaling Unveil Roles for p53 and EGR1 in Elimination of Inconsistent Growth Signals - Zwang, Yaara; Sas-Chen, Aldema; Drier, Yotam; Shay, Tal; Avraham, Roi; Lauriola, Mattia; Shema, Efrat; Lidor-Nili, Efrat; Jacob-Hirsch, Jasmine; Amariglio, Ninette; Lu, Yiling; Mills, Gordon B.; et al. (Molecular cell, 2011)
Normal cells require continuous exposure to growth factors in order to cross a restriction point and commit to cell-cycle progression. This can be replaced by two short, appropriately spaced pulses of growth factors, where the first pulse primes a process, which is completed by the second pulse, and enables restriction point crossing. Through integration of comprehensive proteomic and transcriptomic analyses of each pulse, we identified three processes that regulate restriction point crossing: (1) The first pulse induces essential metabolic enzymes and activates p53-dependent restraining processes. (2) The second pulse eliminates, via the PI3K/AKT pathway, the suppressive action of p53, as well as (3) sets an ERK-EGR1 threshold mechanism, which digitizes graded external signals into an all-or-none decision obligatory for S phase entry. Together, our findings uncover two gating mechanisms, which ensure that cells ignore fortuitous growth factors and undergo proliferation only in response to consistent mitogenic signals. [Display omitted] ► Two pulses of EGF are sufficient to induce entry of mammary cells into S phase ► Induction of metabolic processes during the G1 phase is essential for S phase entry ► Activation of an ERK-EGR1 module sets a threshold for proliferation ► A single pulse of EGF cannot induce proliferation due to early activation of p53.